KAJIAN KARAKTERISTIK SOSIAL EKONOMI MASYARAKT DI NAGARI SUNGAI SARIAK KECAMATAN VII KOTO KABUPATEN PADANG PARIAMAN (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2017)
Abstract his study aims to find out the Social Economy Society in the nagari Sungai Sariak VII Koto district Padang Pariaman viewed from: 1) Social interaction in the community nagari Sariak River district VII Koto Padang Pariaman. 2). Community income in nagari Sungai Sariak subdistrict VII Koto Padang Pariaman. 3). Education community d in nagari Sungai Sariak district VII Koto Padang Pariaman. 4). Public health in the nagari Sungai Sariak subdistrict VII Koto Padang Pariaman .. Type of research used is descriptive. The sample of this research is all head of family living in nagari Sungai Sariak sub district VII Koto Kabupaten Padang Pariaman.91KK. The instrument used in this study is a questionnaire or questionnaire. Data analysis using percentage formula. The results of this study found: 1). Social interaction of community in nagari Sungai Sariak sub district VII Koto Regency of Padang Pariaman in general have good. 2) .The income of the community in the Sariak River village of VII Koto of Padang Pariaman Regency is still insufficient because of the income they earn less so it is difficult for them to fulfill their daily needs. 3). Community education in the nagari Sungai Sariak subdistrict VII Koto Padang Pariaman District still a lot of education is still low as just finished primary school and did not even complete primary school. 4). Public Health in the nagari Sungai Sariak subdistrict VII Koto Padang Pariaman regency, a disease commonly suffered by the public in general is the flu and cough.